Pengaruh Model Pembelajaran Learning Cycle Pada Mata Pelajaran Ilmu Pengetahuan Alam Terpadu Terhadap Aktivitas Belajar Siswa Di Sekolah Menengah Pertama Negeri 22 Kota Jambi - Indo Masse (JEMST (Jurnal of Education in Mathematics, Science, and Technology), 2019)
This study discusses the learning cycle of learning cycles in integrated Natural Sciences subjects towards student learning activities at SMP Negeri 22 Jambi City. This research is a quantitative study using a quasi-experimental design with a posttest only control design, while the data is carried out using a questionnaire. This study found that the use of the cycle learning model had a significant effect on student learning activities at SMP Negeri 22 Jambi City. From the data analysis using the "t" test, it is obtained –table≤ tcount ≤ + ttable or -1.999 ≤ 3.76≤ +1.999 so that H0 is rejected and Ha is accepted. From the calculation of the effect size, it is obtained d = 0.9 with a proportion of 82%. This shows that the learning cycle learning model has a significant effect on student learning activities compared to conventional learning models. Teachers can use the learning cycle learning model in learning activities, especially in Natural Science subjects so that students can actively participate in the learning process.